1996
DOI: 10.1079/bjn19960007
|View full text |Cite
|
Sign up to set email alerts
|

Food photography II: use of food photographs for estimating portion size and the nutrient content of meals

Abstract: The aim of the present study was to determine the errors in the conceptualization of portion size using photographs. Male and female volunteers aged 18-90 years (n 136) from a wide variety of social and occupational backgrounds completed 602 assessments of portion size in relation to food photographs. Subjects served themselves between four and six foods at one meal (breakfast, lunch or dinner). Portion sizes were weighed by the investigators at the time of serving, and any waste was weighed at the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
2
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(198 citation statements)
references
References 14 publications
7
180
2
9
Order By: Relevance
“…Other studies (3,5) have shown the flat slope phenomenon; small portion sizes are overestimated and large portion sizes are underestimated. However, we could not observe this trend in our data.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies (3,5) have shown the flat slope phenomenon; small portion sizes are overestimated and large portion sizes are underestimated. However, we could not observe this trend in our data.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, the participants in the study of Nelson et al (5) had no difficulty in estimating wedges of quiche or mounds of boiled rice.…”
Section: Discussionmentioning
confidence: 93%
“…The full chart can be downloaded at http://www.kcl.ac.uk/ stoolchart Assessment of fecal output in enteral feeding K Whelan et al the consistency and weight combinations. Photographs were added to the chart because the use of verbal descriptors alone may cause misinterpretation of actual fecal consistency (Mertz et al, 1995), while the estimation of food weight is aided by the use of food photographs for comparison (Nelson et al, 1996). The fecal models were made using predetermined quantities of dried mashed potato, food dye and boiling water.…”
Section: Chart Developmentmentioning
confidence: 99%
“…For seasonal foods, such as mangoes, women were asked to estimate their average intake when the food was in season. Portion sizes were estimated on the basis of "natural" units (e.g., 1 egg), or by asking the women to select from previously validated sets of 8 colour photographs that represent different portion sizes 8,9 or by using average portion sizes derived from published sources. 10 -13 Additional questions ascertained the main eating habits (e.g., consumption of alcohol, meat and fish and type of fat used in cooking) and changes throughout life.…”
Section: Food-frequency Questionnaire (Ffq)mentioning
confidence: 99%